Sufi Tradition as Legitimization of Guardianship in The Java: The Study of Manuscripts of Babad Demak Pesisiran - Qolbiyah, Shofwatul (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2024)
The development of Islam in Java is inseparable from the role of wali as a preacher of Islam. The title of wali is given to selected people who get privileges such karamah and knowledge about Islam. This research aims to analyze sufi tradition carried out by Java sufi until they reach the degree of wali. This research uses a qualitative method with descriptive analysis. The research source used is Babad Demak Pesisiran, which was transliterated by the Indonesian Education and Culture Ministry in 1984. The result of this research is about sufi tradition carried out by wali, such as fasting to curb the lust (tan dhahar rikala rina), praying all night long to get closer to God (tan sare rikala wengi), and solitude by meditating in a quiet place such as mountain or home. This condition happened because of Sufi's influence and the mysticism values that developed in Java.